RESPONS KOMUNITAS NELAYAN TERHADAP MODERNISASI PERIKANAN: STUDI KASUS NELAYAN SUKU BAJO DI DESA LAGASA KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - Hamzah, Awaludin (Jurnal AGRISEP, 2009)
Fishery modernization by the Government of Indonesian is intended to alleviate fishery community poverty including for Bajau Ethnic fishermen.  This research is aimed at studying the relationship between the meaning of sea and work by fishermen and their acceptance to fishery modernization, impact analyzing of fishery modernization to work pattern, social structure, and the propesperity level.  This research is conducted in Lagasa Village, District Of Muna Southeast Sulawesi where Bajau ethnic stay.  Respondents consist of 45 ponggawas, 30 local sawies, and 25 sawies from outside village, 5 others as informants. Impacts of modernization to the fisherman community were shown by changes of job pattern that consisted of increasingly the capacity to explore and number of workers (sawi), the character of job tent semi-free labor system, the recruitment of workers became more selective, and the division of labor became more clear and hierarchism. After that, the impacts on the social structure occurred especially on the organizing of sharing holder system that was increasingly more formal, social stratification became more complex, economic activity more differentiated, and the pattern of work relation became semi-exploitative.